Hazard Potential Analysis Using Job Safety Analysis at the Mandala Waluya University Laboratory - Ramadhani, As Samii; Yanti, Fitri; Ulva, Sitti Marya (Universitas Mandala Waluya, 2025)
Potential hazards in laboratories can arise from various sources, such as chemical, physical, ergonomic, biological, and mechanical hazards. This study examines the potential hazards and risk levels in the laboratories of Mandala Waluya University, which include chemical, physical, ergonomic, biological, and mechanical hazards. Using a quantitative descriptive approach through observation, interviews, and Job Safety Analysis (JSA) checklists on five main hazard aspects, risk determination was carried out based on a scale of likelihood and severity, which were classified into low, medium, and high risks. Of the 19 laboratories analyzed, most showed moderate to high risks. Therefore, this analysis focused on three laboratories with moderate to high risks, namely the Pharmaceutical Chemistry Laboratory, the Medical Electrical Technology Laboratory, and the Cytohistology Laboratory, as they had the highest risk levels, particularly related to exposure to chemical and physical hazards and the need to improve the implementation of work safety procedures. These findings emphasize the importance of strengthening risk management through the consistent implementation of K3 standard operating procedures, coupled with increased supervision, safety training, and the provision of adequate personal protective equipment to minimize the potential for accidents and ensure the safety of the academic community.